2018
DOI: 10.1016/j.jmig.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Unsuspected Uterine Sarcoma in an Urban Hospital: Does Surgical Approach Matter?

Abstract: The incidence of unsuspected uterine sarcoma during myomectomy or hysterectomy for benign indications is low at our institution, and is similar for open and MIS cases. Patients should be counseled on the risks and benefits of both open surgery and MIS approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
0
2
1
Order By: Relevance
“…A review of the literature shows that while the incidence of occult uterine leiomyosarcoma in patients who undergo only hysterectomies can be 0.89% at the highest [15], the incidence of occult uterine leiomyosarcoma varies between 0.20% and 0.38% when all patients who underwent hysterectomy and myomectomy are included in the analysis [20,21]. In our study, the incidence of leiomyosarcoma was calculated to be 0.08%, which is relatively lower than that reported in other studies.…”
Section: Discussioncontrasting
confidence: 67%
“…A review of the literature shows that while the incidence of occult uterine leiomyosarcoma in patients who undergo only hysterectomies can be 0.89% at the highest [15], the incidence of occult uterine leiomyosarcoma varies between 0.20% and 0.38% when all patients who underwent hysterectomy and myomectomy are included in the analysis [20,21]. In our study, the incidence of leiomyosarcoma was calculated to be 0.08%, which is relatively lower than that reported in other studies.…”
Section: Discussioncontrasting
confidence: 67%
“…Consequently, there is a risk that patients, initially diagnosed with a large leiomyoma, may undergo MIS without the awareness of an underlying mesenchymal malignancy [21].…”
Section: Introductionmentioning
confidence: 99%
“…Raine-Bennett T et al [16] showed the incidence of occult uterine sarcomas identified during hysterectomies performed for leiomyomas was 1/278 or 3.60 (95% confidence interval [CI] 2.97-4.23) per 1000 hysterectomies. The incidence was similar in open abdominal surgery and laparoscopy (3/743 vs. 1/1216; p = 0.16) [21]. In 2014 FDA stated that tumor morcellation used for laparoscopic myomectomy or hysterectomy is associated with increased risk for spreading cancer and restricts the usage of tumor morcellation [22].…”
Section: Introductionmentioning
confidence: 99%